Pengaruh Corporate Social Reponsbility (CSR), Biaya Lingkungan Dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Vina Rismawati; Indriastuti, Maya (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR), environmental expenditures, and company size on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. “Financial performance is evaluated by Return on Assets (ROA). This study utilizes a quantitative technique defined by an explanatory research design. Secondary data were obtained from the annual and sustainability reports of 31 mining companies, resulting in 93 observational data points. Data analysis was performed using multiple linear regression after doing standard assumption tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. The results demonstrated that environmental expenditures positively and significantly impacted financial performance. This indicates that investment in environmental management may improve a company's reputation and stakeholder confidence, therefore favorably affecting financial performance. In contrast, Corporate Social Responsibility (CSR) disclosure and company size do not have a substantial impact on financial performance. This suggests that CSR disclosure may not inspire full market trust or may be only symbolic, and a company's asset size does not automatically guarantee enhanced financial performance in the mining sector, which is heavily affected by commodity price fluctuations and operational efficiency.